A Case Report: Side Effect Of Linezolid In Pulmonary Rifampicin Resistance Tuberculosis - Mustofa, Syazili; Karina, Salwa Al; Putri, Giska Tri; Busman, Hendri; Syakir, Muhammad Addin (Jurnal Ilmu Kedokteran dan Kesehatan, 2025)
Linezolid is a very potent treatment for pulmonary tuberculosis, but it has some side effects. Patients with drug-resistant pulmonary tuberculosis may experience anemia as a side effect of taking the multidrug-resistant tuberculosis medication Linezolid. A 58-year-old man's primary complaint in one case reported to RSUD dr. H. Abdul Moeloek Lampung was a weakness. The diagnosis was made based on anamnesis, a physical examination, and supporting examinations. Treatment was given both pharmacologically and non-pharmacologically, including the intervention to discontinue Linezolid. Although linezolid-based combination therapy in program conditions is associated with favorable outcomes, side effects should be monitored closely, which may require discontinuation of the drug and taking appropriate steps to treat side effects.